ANALISIS DAMPAK IMPLEMENTASI ARSITEKTUR PERBANKAN INDONESIA (API) TERHADAP KINERJA PERBANKAN INDONESIA - Ezeddin, Sucitra Nindia; Wijaya, Errin Yani (Jurnal Tepak Manajemen Bisnis, 2014)
This study aims to determine the impact of the implementation of the Indonesian Banking Architecture ( API ) that dilakukanh by Bank Indonesia against general banking in Indonesia . This study was conducted to all national banks in Indonesia in the period 2000-2008 , amounting to 48 commercial banks . In order to see the impact of the implementation of the API is measured by a comparison of the financial performance indicators of banking , namely ROA , CAR , ROA , NIM and LDR . In testing hypotheses make use of statistical analysis using the paired difference test using SPSS analysis tools . The results showed that for the variable ROA there is no difference in performance before and after the enforced API which 0.203 t < t table 1.679 . The variable CAR is also no difference before and after the performance of the API which imposed -0913 t < t table 1.679 . V ariable BOPO ther e was no differ ence before and after the performance of the API which imposed -1206 t < t table 1.679 . LDR variables there was no difference before and after the performance of the API which imposed -8194 t < t table from 1697 , while the only ratio that has a performance difference before and after the API is implemented NIM ratio where 2,475 t count > t table 1.679 . Overall it can be concluded that after the imposition of financial performance ratios API banking experience better performance changes seen only on variables NIM but other than that the two ratios , namely ROA and CAR began to show the direction of improvement compared to the other two , namely the ratio of ROA and LDR are not shown direction of improvement at all . This indicates that in terms of efficiency and good governance and true banking does not meet the desired expectations of the spirit of the API .Keywords : API , Banks , Performance ,